Iliac fossa vs Pfannenstiel retrieval incision in laparoscopic donor nephrectomy: A critical analysis. Issue 4 (2nd October 2019) - Deshmukh, Chaitanya S.; Ganpule, Arvind P.; Sudharsan, S. Balaji; Singh, Abhishek G.; Sabnis, Ravindra B.; Desai, Mahesh R.
ABSTRACT: Objective : To compare two retrieval incisions, Pfannenstiel vs iliac fossa incision, in terms of operative technique-related variables and variables related to patient satisfaction postoperatively, in patients undergoing laparoscopic donor nephrectomy (LDN). Patients and methods : This prospective randomised study was conducted between May 2016 and April 2017. All the voluntary kidney donors aged 18–60 years were randomised into two groups. Group 1, comprised patients undergoing graft retrieval via an iliac fossa incision, and Group 2 comprised those undergoing graft retrieval via a Pfannenstiel incision. Intraoperative assessment of the incision by the surgeon was done using a Likert scale-based questionnaire. Other variables studied were the operative time, retrieval time, warm ischaemia time, and length of incision. Postoperatively, visual analogue scale pain scores, analgesia consumption, and hospital stay were compared. During follow-up cosmetic outcome was compared. Results : In all, 108 patients were enrolled in the study with 54 patients in each group. The mean operative time was shorter in Pfannenstiel-incision group, at 155.2 vs 171.67 min ( P  = 0.01). The retrieval incision length was significantly less in the Pfannenstiel arm, at 9.29 vs 9.85 cm ( P  < 0.001). In the surgeon Likert scale-based questionnaire, the Pfannenstiel incision scored better than the iliac fossa incision for ease of specimen retrieval ( P  = 0.015), ease of immediate check laparoscopy ( P  = 0.002), and ease of incision closure ( P  < 0.001). The Pfannenstiel-incision group required less postoperative analgesia, at a mean (SD) of 7.03 (8.82) vs 15.55 (11.1) mg nalbuphine ( P  < 0.001). During follow-up the Manchester Scar Scores were lesser in the Pfannenstiel-incision group ( P  < 0.001). Conclusion : The Pfannenstiel incision was considered preferable during the critical steps of the LDN and had a smaller retrieval incision, lesser operative time and postoperative analgesia requirement, and better cosmesis than the iliac fossa incision. Abbreviations: BMI: body mass index; LDN: laparoscopic donor nephrectomy; VAS: visual analogue scale; WIT, warm ischaemia time